Insecure adult attachment style is associated with elevated psychological symptoms in early adjustment to severe burn: A cross-sectional study. Issue 6 (September 2019) - Holt, Rachael; Kornhaber, Rachel; Kwiet, Julia; Rogers, Vanessa; Shaw, Joanne; Law, Jeremy; Proctor, Marie-Thérèse; Vandervord, John; Streimer, Jeffrey; Visentin, Denis; Cleary, Michelle; McLean, Loyola
Highlights: Hospitalised burn patients reporting a secure adult attachment style reported less psychological distress. Hospitalised burns patients reporting a secure adult attachment style reported less post-traumatic stress. Insecure attachment may be a risk factor for poorer psychological adjustment in those hospitalised for severe burn injury. Abstract: Research into recovery and adjustment after burn injury has indicated a link between psychopathological symptoms including traumatic stress, distress, depression and anxiety, and worse psychosocial and physical outcomes. The severity of psychological symptoms does not always correlate with that of the burn injury, and symptoms can be ongoing in certain patients for extensive periods, leading to a need for early screening in burns patients for psychological vulnerabilities. One potential factor influencing recovery from the psychological impact of burn injury is adult attachment style, specifically secure and insecure attachment, as this describes how an individual organizes their stress regulation. This cross-sectional study measured: (a) attachment style (via the Relationship Questionnaire [RQ]): (b) negative psychological symptoms (via the Depression Anxiety and Stress Scale [DASS]); and, (c) post-traumatic symptoms (via the Davidson Trauma Scale [DTS]) in a cohort of burns patients (n = 104, 51 analysed) in a severe burns unit in Australia during the acute phase of their recovery. Secure attachment style was inversely related to psychopathological symptoms. Secure participants scored significantly lower scores on the DASS (M = 17.63, SD = 17.07) compared to self-rated insecure participants [(M = 42.38, SD = 34.69), p < .01] and on the DTS (M = 14.22, SD = 15.42) compared to insecure participants [(M = 40.54, SD = 35.72), p < .01]. Similar results were found in analyses controlling for covariates of gender, age and burn severity as potential confounders. This research suggests attachment style may play an important role in psychosocial recovery from severe burn injury.